Walkable cities : revitalization, vibrancy and sustainable consumption - Balsas, Carlos J. L., 1971- (State University of New York Press, 2019)
Examines how cities of various sizes on both sides of the Atlantic Ocean are making walkability improvements a part of their overall urban revitalization strategy. Walkable precincts have become an important component of urban revitalization on both sides of the Atlantic. In Walkable Cities, Carlos J.L. Balsas examines a range of city scales and geographic settings on three continents, focusing on the Iberian Peninsula (Spain and Portugal), Latin America (Brazil and Mexico), and the United States (Phoenix and New York City). He explains how this "pedestrianization of Main Street" approach to central locations (downtowns and midtowns) has contributed to strengthening various urban functions, such as urban vitality, pedestrian and bicyclist safety, tourism, and more. However, it has also put pressure on less affluent, peripheral, and fragile areas due to higher levels of consumption and waste generation. Balsas calls attention to the need to base urban revitalization interventions on more spatially and socially just interventions coupled with sustainable consumption practices that do not necessarily entail high growth levels, but instead aim to improve the quality of city life. Carlos J.L. Balsas is Assistant Professor of Urban Planning at the University at Albany, State University of New York
Keywords: Urban renewal -- United States.; Urban renewal -- Europe.; Sustainable urban development -- United States.; Sustainable urban development -- Europe.; Walking -- United States.; Walking -- Europe.; Rénovation urbaine -- États-Unis.; Rénovation urbaine -- Europe.; Urbanisme durable -- États-Unis.; Urbanisme durable -- Europe.; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development.; Sustainable urban development; Urban renewal; Walking; Europe; United States